2022
DOI: 10.1177/09544062221074605
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on pressure fluctuations of dual - and analogical single-rotor turbine flowmeters

Abstract: As a cutting-edge technology in the field of flow measurement, a dual-rotor turbine flowmeter is introduced into the refined measurement in hypersonic flight. In this study, to assess the characteristics of internal pressure fluctuation in the flowmeter, unsteady numerical calculations were performed using rotor motion programs, and the same method was applied to an analogical single-rotor turbine flowmeter. The frequency content, generation reasons, and propagation laws were analysed and compared. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Pressure signals were collected for 10 revolutions after the rotors have evenly rotated for 20 revolutions. This normalized pressure coefficient is defined to characterize the degree of pressure fluctuation, 34 expressed as where C p is the normalized pressure coefficient; p is the pressure of measuring points (Pa); p false¯ is the average pressure of measuring points within the sampling time (Pa); ρ is the mixing density (kg/m 3 ); U is the impeller outlet circumferential velocity (m/s). To research the frequency characteristics, the FFT was applied to these measuring points.…”
Section: Numerical Modeling and Schemesmentioning
confidence: 85%
See 1 more Smart Citation
“…Pressure signals were collected for 10 revolutions after the rotors have evenly rotated for 20 revolutions. This normalized pressure coefficient is defined to characterize the degree of pressure fluctuation, 34 expressed as where C p is the normalized pressure coefficient; p is the pressure of measuring points (Pa); p false¯ is the average pressure of measuring points within the sampling time (Pa); ρ is the mixing density (kg/m 3 ); U is the impeller outlet circumferential velocity (m/s). To research the frequency characteristics, the FFT was applied to these measuring points.…”
Section: Numerical Modeling and Schemesmentioning
confidence: 85%
“…Pressure signals were collected for 10 revolutions after the rotors have evenly rotated for 20 revolutions. This normalized pressure coefficient is defined to characterize the degree of pressure fluctuation, 34 expressed as…”
Section: Numerical Methods and Boundary Conditionsmentioning
confidence: 99%
“…In the research of dual-rotor turbine flow meters, the rotor response, combined with visualization experiments and unsteady simulations, was investigated by Ren et al [1,2]. Their research showed that the downstream rotor speed compensates for speed calculation, reducing measurement instability of the upstream rotor.…”
Section: Introductionmentioning
confidence: 99%